Pemberian Edukasi Lansia SMART Untuk Mencegah Penyebaran Covid-19 di Wilayah Kerja Puskesmas Taratara - David, Brigitte; Natalia, Fina; Terok, Kansia; Toreh, Pricilia (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
The new order that has emerged due to the Covid-19 pandemic has forced people to adapt in their lives. So a new challenge is related to public information related to Covid-19, community behaviour, Covid-19 vaccination, and the use of health services. The most vulnerable group is the elderly, so there is a need for direct educational activities for the elderly about the Coronavirus, and how to prevent it. This community service program is carried out in the work area of the Tara-tara Health Center with the aim of providing education to the elderly. This activity uses the method of providing direct education in the form of lectures, discussions and questions and answers. The results of this service activity are increasing the understanding and knowledge of the elderly about the Corona Virus and how to maintain health during a pandemic from co-morbidities so that the elderly can be healthy and happy. In conclusion, this educational activity must be carried out continuously by paying attention to health protocols during the pandemic.